Oncologists' Perspectives on Individualizing Dose Selection for Patients With Metastatic Cancer. Issue 11 (20th November 2022) - Jimenez, Rachel B.; Schenkel, Caroline; Levit, Laura A.; Hu, Bonnie; Lei, Xiudong Jennifer; Harvey, R. Donald; Morrison, Vicki A.; Pollastro, Teri; Waterhouse, David; Weekes, Colin; Williams, Grant R.; Bruinooge, Suanna; et al.
Abstract : PURPOSE: Treatment goals for patients with metastatic cancer include prolongation and maintenance of quality of life. Patients and oncologists have questioned the current paradigm of initial dose selection for systemic therapy; however, data on oncologists' dose selection strategies and beliefs are lacking. METHODS: We conducted an electronic international survey of medical oncologists who treat patients with breast and/or gastrointestinal cancers. Survey questions addressed experiences with, and attitudes toward, dose reduction at initiation (DRI) of a new systemic therapy for patients with metastatic cancer. RESULTS: Among 3, 099 eligible oncologists, 367 responded (response rate 12%). Most (52%) reported using DRI at least 10% of the time to minimize toxicities. Gastrointestinal specialists were more likely to report DRI ≥ 10% of the time (72% v 50% of generalists and 51% of breast specialists, P < .005). Of those who dose reduced ≥ 10% of the time, 89% reported discussing potential tradeoffs between efficacy and toxicity with patients. Overall, 65% agreed it is acceptable to lower starting doses to reduce side effects even if it compromises efficacy; younger clinicians were more likely to agree ( P < .005). There was strong support (89%) for future trials to determine optimal effective, rather than maximum tolerated, dose. CONCLUSION: Oncology practice varies with regard to discussion and individualized selection of starting doses in the metastatic setting. This study demonstrates a need for consideration of shared decision making regarding initial dose selection and strong support among oncologists for clinical studies to define optimal dosing and best practices for individualizing care.